The Natural Growth Rate of Residual Juvenile Angiofibroma - Rowan, Nicholas R.; Stapleton, Amanda L.; Heft-Neal, Molly E.; Gardner, Paul A.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives Examine the postoperative growth rate of residual juvenile angiofibroma (JA) in a large series of patients relative to pediatric growth parameters and other prognostic factors. Establish an algorithm for postoperative surveillance of patients with JA.Design Retrospective case series.Setting Tertiary referral academic center.Participants Pediatric patients undergoing surgical resection of JA between September 2005 and June 2015.Main Outcome Measures Postoperative recurrence and tumor growth rates.Results Thirty-eight patients were identified with a mean follow-up of 24.1 months. Sixty-eight percent (26/34) of patients achieved gross total resection, and 32% (12/38) had persistent postoperative disease. Of those with postoperative residual tumor, all had preoperative skull base involvement and residual blood supply from the internal carotid artery following embolization. Sixty-seven percent (8/12) of patients with postoperative residual tumor demonstrated radiographic stability of disease with scans being completed approximately every 6 months. Radiographic rates of disease progression ranged from 4.1 to 9.22 mm/year.Conclusions Patients with preoperative skull base involvement and residual vascularity following preoperative embolization are more likely to have residual postoperative disease, and a longer postoperative follow-up is warranted in these patients. Progression of residual disease occurred approximately 7.5 months postoperatively. Younger patients may be more likely to need further intervention for postoperative residual disease, and postoperative imaging at 6-month intervals appears appropriate.
Keywords: Angiofibroma; surgery; endoscopy; staging system; prognosis; skull base; pathology